Child behavior in educational contexts: Contributions of the notion of Behavior Settings - Farinha, José (2019)
According to the theoretical perspective of ecological dynamics, children's behavior emerges from the interaction that is established between their own characteristics and the context in which the behavior occurs. However, the focus of educational action has been primarily on children, their characteristics and needs, and the environment in which they learn and develop has not always received the attention they deserve. Based on Roger Barker's concept of behavior setting, there are repetitive patterns of behavior that are characteristic of particular locations and certain time limits. There is a mutual and reciprocal relationship between the participants and the environment that constitutes the behavior settings, which conditions the possibilities of action of their actors. The child, in his daily life, acts as a participant in various behavior setting. In this paper we aim to show the importance of contextual characteristics in children's behavior, developmental and learning processes.